Picornavirus 2C proteins: structure-function relationships and interactions with host factors - Yin, Chunhui; Zhao, Haomiao; Xia, Xiaoyi; Pan, Zhengyang; Li, Daoqun; Zhang, Leiliang (Frontiers in Cellular and Infection Microbiology, 2024)
Picornaviruses, which are positive-stranded, non-enveloped RNA viruses, are known to infect people and animals with a broad spectrum of diseases. Among the nonstructural proteins in picornaviruses, 2C proteins are highly conserved and exhibit multiple structural domains, including amphipathic α-helices, an ATPase structural domain, and a zinc finger structural domain. This review offers a comprehensive overview of the functional structures of picornaviruses’ 2C protein. We summarize the mechanisms by which the 2C protein enhances viral replication. 2C protein interacts with various host factors to form the replication complex, ultimately promoting viral replication. We review the mechanisms through which picornaviruses’ 2C proteins interact with the NF-κB, RIG-I, MDA5, NOD2, and IFN pathways, contributing to the evasion of the antiviral innate immune response. Additionally, we provide an overview of broad-spectrum antiviral drugs for treating various enterovirus infections, such as guanidine hydrochloride, fluoxetine, and dibucaine derivatives. These drugs may exert their inhibitory effects on viral infections by targeting interactions with 2C proteins. The review underscores the need for further research to elucidate the precise mechanisms of action of 2C proteins and to identify additional host factors for potential therapeutic intervention. Overall, this review contributes to a deeper understanding of picornaviruses and offers insights into the antiviral strategies against these significant viral pathogens.